QUALITY OF DIRECT CASH ASSISTANCE SERVICES AFFECTED BY COVID-19 ON COMMUNITY SATISFACTION OF DIRECT CASH ASSISTANCE RECIPIENTS IN PEJENG VILLAGE GIANYAR REGENCY, BALI PROVINCE - Ida Ayu Putu Sri Widnyani; Cok Gde Agung Kusuma Putra; Nyoman Diah Utari Dewi; A.A. Gede Raka (DIA: Jurnal Administrasi Publik, 2021)
Pejeng Village Government Services in Handling Covid-19 in the Village through the Village APB by distributing Direct Cash Assistance (BLT) to the community. The quality of BLT distribution services in Pejeng Village will have an impact on community satisfaction. There were problems related to the BLT distribution that was not right on target. This condition is the background of this study to determine whether responsiveness, reliability, assurance, concern, and tangibles partially and simultaneously affect the satisfaction of the people of Pejeng Village, Gianyar Regency. The method used in this research uses a quantitative descriptive approach. The purpose of this study was to determine and analyze the effect of responsiveness, reliability, assurance, empathy, and tangibles on community satisfaction Pejeng Village. The results showed that responsiveness, reliability, assurance, empathy, and tangibles partially and simultaneously had a positive and significant effect on community satisfaction in Pejeng Village, Gianyar Regency.